What publishers can take away from the latest early career researcher research - Nicholas, David; Watkinson, Anthony; Abrizah, Abdullah; Boukacem-Zeghmouri, Cherifa; Xu, Jie; Rodriguez-Bravo, Blanca; Swigon, Marzena; Herman, Eti (Wiley, 2018)
Key points Early career researchers (ECRs) consider journals the central form of communication – but are concerned about pressure to publish. ECRs want to share but currently accept the closed publishing system because of the need to build a traditional reputation. ECRs know – and appear to care – little about publishers but trust them as publishing and reviewing facilitators. Editors are criticized for not managing peer review with better selection of reviewers. Megajournals are not seen as the future journal form and criticized for lack of selectivity. ECRs want open access/science in principle but are circumspect about their contribution to it. ResearchGate is a key force for change as ECRs consider it a mainstay communication and reputation platform.